Mesial Temporal Lobe Epilepsy (MTLE) Drug-Refractoriness Is Associated With P2X7 Receptors Overexpression in the Human Hippocampus and Temporal Neocortex and May Be Predicted by Low Circulating Levels of miR-22 - Guerra Leal, Bárbara; Barros-Barbosa, Aurora; Ferreirinha, Fátima; Chaves, João; Rangel, Rui; Santos, Agostinho; Carvalho, Cláudia; Martins-Ferreira, Ricardo; Samões, Raquel; Freitas, Joel; Lopes, João; Ramalheira, João; et al. (Frontiers in Cellular Neuroscience, 2022)
Objective: ATP-gated ionotropic P2X7 receptors (P2X7R) actively participate in epilepsy and other neurological disorders. Neocortical nerve terminals of patients with Mesial Temporal Lobe Epilepsy with Hippocampal Sclerosis (MTLE-HS) express higher P2X7R amounts. Overexpression of P2X7R bolsters ATP signals during seizures resulting in glial cell activation, cytokines production, and GABAergic rundown with unrestrained glutamatergic excitation. In a mouse model of status epilepticus, increased expression of P2X7R has been associated with the down-modulation of the non-coding micro RNA, miR-22. MiR levels are stable in biological fluids and normally reflect remote tissue production making them ideal disease biomarkers. Here, we compared P2X7R and miR-22 expression in epileptic brains and in the serum of patients with MTLE-HS, respectively. Methods: Quantitative RT-PCR was used to evaluate the expression of P2X7R in the hippocampus and anterior temporal lobe of 23 patients with MTLE-HS and 10 cadaveric controls. Confocal microscopy and Western blot analysis were performed to assess P2X7R protein amounts. MiR-22 expression was evaluated in cell-free sera of 40 MTLE-HS patients and 48 healthy controls. Results: Nerve terminals of the hippocampus and neocortical temporal lobe of MTLE-HS patients overexpress (p < 0.05) an 85 kDa P2X7R protein whereas the normally occurring 67 kDa receptor protein dominates in the brain of the cadaveric controls. Contrariwise, miR-22 serum levels are diminished (p < 0.001) in MTLE-HS patients compared to age-matched control blood donors, a situation that is more evident in patients requiring multiple (>3) anti-epileptic drug (AED) regimens. Conclusion: Data show that there is an inverse relationship between miR-22 serum levels and P2X7R expression in the hippocampus and neocortex of MTLE-HS patients, which implies that measuring serum miR-22 may be a clinical surrogate of P2X7R brain expression in the MTLE-HS. Moreover, the high area under the ROC curve (0.777; 95% CI 0.629–0.925; p = 0.001) suggests that low miR-22 serum levels may be a sensitive predictor of poor response to AEDs among MTLE-HS patients. Results also anticipate that targeting the miR-22/P2X7R axis may be a good strategy to develop newer AEDs.